Despesas públicas municipais e desenvolvimento socioeconômico local: SUR Espacial e Painel Probit Ordenado aplicados aos municípios brasileiros - Vitor Salomão Mourão (2024)
The objective of the dissertation was to evaluate the sensitivity of the local socioeconomic development of Brazilian municipalities – measured by the Firjan Municipal Development Index – to municipal public expenditure per capita and, additionally, to test whether this sensitivity is influenced by the degree of fiscal autonomy, productive and sociodemographic characteristics of the municipalities. The relationship of interest was empirically tested based on data from Brazilian municipalities using the Spatial SUR, due to the identification of spatial autocorrelation between socioeconomic development indicators, and the Ordered Probit Panel, given the possible non- linearity between variables. Data from 2005, 2010 and 2016 were used. The results of the spatial SUR and the Ordered Probit Panel corroborated the hypothesis of the capacity of municipalities to act in favor of local socioeconomic development. The models suggest the sensitivity of the Firjan Municipal Development Index to local government expenditures related to resource allocation. The estimators of municipal public expenditure per capita in administration, health, social security and culture were significant and positive in the spatial SUR. The marginal effects of per capita expenditure on administration, health, social security, culture and sanitation were significant and positive, analyzing the probability of municipalities belonging to the High standard of development category in the Ordered Probit Panel. An important caveat for the result, however, is that the municipal public expenditure estimators had a low effect compared to the other structural characteristics of the municipalities, mainly in relation to fiscal autonomy.